Continuum of non-alcoholic fatty liver disease: from hepatic steatosis to cardiovascular risk - O. M. Drapkina; O. N. Korneeva (Рациональная фармакотерапия в кардиологии)
The problem of non-alcoholic fatty liver disease (NAFLD), which is an independent risk factor for a number of cardiovascular diseases (CVD), is considered. The high prevalence of cardiovascular risk factors is demonstrated in patients with NAFLD in Russian population. Common pathophysiological mechanisms of NAFLD and CVD (insulin resistance and excessive accumulation of lipids in the liver) are discussed. The "new" risk factors (thickening of the pericardial fat, endothelial dysfunction, thickening of the intima-media complex, increase in plasma level of C-reactive protein and others.) are found in patients with NAFLD, along with a greater prevalence of traditional factors of CVD risk (obesity, diabetes, metabolic syndrome and etc.). The relationship of NAFLD with atherosclerosis, dyslipidemia, features of bile acids metabolism in NAFLD and ability to influence these components are also considered.